Nurses Work Functioning Questionnaire (NWFQ): refinement and validation of the Italian version - Magnavita, Nicola; Chiorri, Carlo (La Medicina del Lavoro, 2017)
Background: The availability of an assessment measure for work impairment in nurses, or nursing students, is of crucial importance for early detection of workers/students at risk. Recently, a new measure, the Nurses Work Functioning Questionnaire (NWFQ), has become available, but there is no validated Italian version. Objectives: The aim of this study was to develop and validate an Italian version of the NWFQ. Methods: We evaluated the factor structure, the internal consistency, and the convergent and discriminant construct validity with respect to organizational justice and job strain of the Italian NWFQ using data from 645 nursing students. Results: Results suggested that a single-factor, 34-item measurement model could be a more parsimonious alternative (CFI=.915, TLI=.910, RMSEA=.039 e CFI=.907, TLI=.901, RMSEA=.046 in in two random subsamples; median factor loading .50, range .26-.63) to the original seven-factor structure. The score on this version of the NWFQ showed excellent internal consistency and construct validity, as higher scores were significantly associated with lower perceived distributive (r=-.30) and interpersonal justice (r=-.43), decision latitude (r=-.33), and social support (r=-.58). Conclusions: The Italian refinement of the NWFQ seems to have adequate psychometric properties and it is thus suitable for the assessment of impairment of work functioning in nursing students.